Metacognitive strategies to develop reading understanding - Berrocal, Marina (2019)
This research seeks to promote the development of reading comprehension through the application of metacognitive strategies, as well as to publicize the importance of metacognition processes at different reading levels and the usefulness of designing teaching units that meet specific learning needs. For this, a qualitative - descriptive study was carried out with students in the third and fourth grades of primary school, in which the data obtained from the application of a didactic unit were analyzed, which included questionnaires in which the use was encouraged of metacognitive strategies (previous knowledge, prediction and verification and summary). Similarly, the metacognitive processes of: planning, monitoring and evaluation, worked at different times of reading (before, during and after) were taken into account. The results obtained show that metacognitive strategies make it possible to improve and promote reading comprehension processes because they offer the subject tools that help them monitor, control, evaluate and become aware of their learning process.